American State Ballot Initiatives and Income Inequality - Dyck, Joshua J. (2019)
Some have argued that the ballot initiative process prevalent in many American states might lower inequality. We contend this is improbable based on what is known about whether expansion of democracy leads to redistribution, the attitudes of citizens, and the characteristics of the initiative process. Nevertheless, the proposition needs testing. We examine three types of evidence. First, we analyze the content and passage of all post-World War II initiatives going to voters in California, a state that makes heavy use of ballot propositions. Second, we model institutional factors influencing differences in inequality at the state-level from 1976–2014 to test the aggregate-level effect of ballot initiatives on income inequality. Third, we use individual level data to evaluate the claim that frequent initiative use makes lower income people happier because it helps to reduce inequality. Our analyses consistently indicate that the ballot initiative process fails to reduce income inequality.